Frequency Of Diabetic Retinopathy In Known Diabetic Patients Visiting The Eye Clinic Severity Distribution, Associated Risk Factors. - Khan, Jehanzeb; Rafiq, Muhammad; Waseem, Muhammad; Zeeshan Tahir, Muhammad; Hamza, Syed Amir; Sultan, Maria (Journal of Neonatal Surgery, 2025)
most common causes of blindness. The impact of DR is increasing and is most prevalent in the low- and middle-income countries of the world, where screening is still virtually nonexistent. Assessing the prevalence and severity of DR in already diagnosed diabetics is of great importance in establishing a basis for the prompt initiation of targeted interventions aimed at mitigating vision loss. Objectives: To establish how common and how serious diabetic retinopathy is among diabetic patients going to the eye clinic, as well as to determine principal associated risk factors: duration of the diabetes condition, high blood pressure, and poor control of glycemia. Methodology: this study conducted at department of Ophthalmology, Gajju Khan Medical College Swabi from july to dec 2024.One hundred diabetic participants aged 18 years and older were recruited in a cross-sectional study at an ophthalmology clinic. HbA1c levels were checked, and clinic-demographic data, comorbid conditions, and diabetes duration were collected. All participants underwent slit-lamp bio microscopy after pupillary dilation with an examination of the microscope after diabetic retinopathy (DR) had been graded with the International Clinical DR Classification. All data were input into SPSS 24.0, and simple computations (frequencies, percentages, means, and standard deviation) were calculated. The chi-square test was employed to assess the relationships among variables and DR. Independent factors were identified using logistic regression analysis. A two-tailed p-value of 0.05 was employed as the threshold for statistical significance. Results: 100 diabetic patients with an average age of 55.4 ± 10.2 years, 59% of the sample were male. 42% of the diabetic patients had diabetic retinopathy. In terms of severity, 14% had mild NPDR, 16% had moderate NPDR, 5% had severe NPDR and 7% had PDR. Diabetic macular edema was evident within 11% of the patients. HbA1c (≥8%) demonstrated a significant relationship with DR due to poor glycemic control (p=0.003). Diabetic patients who had had the disease for more than 10 years had DR at a significantly (p=0.001) higher rate. In terms of associations, hypertension was significant (p=0.04) while the variable of gender was not (p=0.28). In the logistic regression HbA1c≥8% (OR 3.8) along with duration of diabetes (OR 4.1) and hypertension (OR 1.9) were significant. Conclusion: All patients diagnosed with diabetes have diabetic retinopathy, with almost half of them having some sort of involvement of the tracheae. Diabetic retinopathy (DR) has an even greater risk factor with increased years of diabetes, poor glycemic control, and high blood pressure. These results should highlight the importance of regular eye examinations, better control of diabetes without complications, and early referrals to help prevent vision loss. Improving vision loss assessments in those who have diabetes should be a major focus to alleviate the impact of unnecessary sight loss in these patients